Recruited monocytes modulate malaria‐induced lung injury through CD36‐mediated clearance of sequestered infected erythrocytes. Issue 5 (29th October 2015) - Lagassé, H. A. Daniel; Anidi, Ifeanyi U.; Craig, John M.; Limjunyawong, Nathachit; Poupore, Amy K.; Mitzner, Wayne; Scott, Alan L.
Abstract : Recruited monocytes limit ALI by clearing parasite‐infected cells via a CD36‐mediated mechanism. Abstract : Pulmonary complications occur in a significant percentage of adults and children during the course of severe malaria. The cellular and molecular innate immune mechanisms that limit the extent of pulmonary inflammation and preserve lung function during severe Plasmodium infections remain unclear. In particular, the contributions to pulmonary complications by parasitized erythrocyte sequestration and subsequent clearance from the lung microvasculature by immune cells have not been clearly defined. We used the Plasmodium berghei ANKA‐C57BL/6 mouse model of severe malaria to investigate the mechanisms governing the nature and extent of malaria‐associated lung injury. We have demonstrated that sequestration of infected erythrocytes on postcapillary endothelial surfaces results in acute lung injury and the rapid recruitment of CCR2 + CD11b + Ly6C hi monocytes from the circulation. These recruited cells remain in the lungs as monocyte‐derived macrophages and are instrumental in the phagocytic clearance of adherent Plasmodium berghei ‐infected erythrocytes. In contrast, alveolar macrophages do not play a significant role in the clearance of malaria‐infected cells. Furthermore, the results obtained from Ccr2 −/−, Cd36 −/−, and CD36 bone marrow chimeric mice showed that sequestration in the absence of CD36‐mediated phagocytic clearance by monocytes leads to exaggerated lung pathologic features. In summary, our data indicate that the intensity of malaria‐induced lung pathologic features is proportional to the steady‐state levels of Plasmodium ‐infected erythrocytes adhering to the pulmonary vasculature. Moreover, the present work has defined a major role of recruited monocytes in clearing infected erythrocytes from the pulmonary interstitium, thus minimizing lung damage.